Rancang Bangun Aplikasi Patroli Security/Satpam Berteknologi NFC (Near Field Communication) dan Google Maps API sebagai Service Data Spasial berbasis Android - Ovriawan Aldo Pribadi Putra; Barlian Henryranu Prasetio; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The recovery of living conditions after the pandemic has forced the community to start designing and reorganizing their business, be it a business in the form of a product or a service. Nevertheless, the security of business or business assets must remain a top priority. So in practice, professional security services are needed with the latest technology to minimize unwanted things while on duty/patrolling in the security area. Now conventional methods are slowly being replaced by digital patrolling innovations. Astha Slur: Security Labor Utility Remote is a digital security patrol application with NFC (Near Field Communication) technology and Google Maps API as an Android-based spatial data service. NFC itself is a radio frequency communication technology that can read addresses on tags as a reader. At the same time, the Google Maps API is a technology that is used for mapping in security areas. Both of these technologies can record situations and conditions in real-time and applications embedded with the Android OS can be easily operated by all security personnel.